AB0448 Real Time Sonoelastography in Primary Sjögren's Syndrome Correlates with Morphological Ultrasonographic Features and Glandular Activity but Not with Minor Salivar Gland Fibrosis. (15th July 2016) - Hernandez-Molina, G.; Criales, S.; Azpeitia, L.; Pacheco, C.; Reyes, E.; Lima, G.; Llorente, L.; Kimura-Hayama, E.
Abstract : Background: Real time sonoelastography (RTS) is a novel imaging option involving tissue stiffness assessment that might be a useful in primary Sjögren's syndrome (PSS). Objectives: To evaluate the stiffness of parotid and submandibular glands using RTS, and to correlate with a morphologic ultrasonographic (US) score, profibrotic chemokines and cytokines, and gland fibrosis among patients with PSS. Methods: We included 26 PSS patients with salivary gland biopsy within 5 years previous the US evaluation. B-Mode US and RTS (ARFI technique) were performed by a trained radiologist. Parotid and submandibular glands were individually rated for parenchymal echogenicity, homogeneity, hypoechogenic areas, hyperechogenic reflections and clearness of borders using the Hocevar scale (Global B-mode sum score 0–48 points). RTS was conducted at both parotid and submandibular glands (8 areas of each gland to obtain a median value) and then reported a median global RTS score in m/seg. We assessed the ESSDAI, ESSPRI, non-stimulated whole salivary flow rate (NSWSF), C3 and C4 levels, RF, anti-Ro/La antibodies and salivary levels of CXCL14, CCL28, TRAIL and TGb measured by ELISA. We also evaluated the presence of fibrosis in biopsies with the Masson's trichrome staining. Results: The mean age was 51.1±11 years, median disease duration of 6.1 years, 92.8% were females and 92.8% had oral symptoms. The global B-mode score was 22.2 points (13–44) and the RTS global score 2.5 (1.64–3.28) m/seg. We found a correlation between the RTS global score and the global B-mode score (t=0.53, p=0.001), the RTS global score between both parotids (t=0.58, p=0.0001) and both submandibulars (t=0.50, p=0.0001); but not between parotids and submandibular glands. The RTS global score correlated with the NSWSF (t=-0.53, p=0.001), ESSDAI (t=0.31, p=0.03), glandular ESDDAI domain (t=0.36, p=0.02), C4 levels (t=-0.32, p=0.04), but not with the rest of serological variables, chemokines and cytokines levels. We found fibrosis in 7 patients (26.9%), and these patients were not different when compared to the group without it, regarding the RTS global score, B-mode global score, age and chemokine and cytokines levels, but tended to have a longer disease duration. At the linear regression analysis, the glandular ESSDAI domain (B=0.49, p=0.04), the C4 level (B=-0.02, p=0.05) and the disease duration (B=0.04, p=0.04) were associated with the RTS global score. Conclusions: The elastrographic evaluation correlated with the US morphologic score and glandular activity but not with fibrosis. References: Dejaco C, De Zordo T, Heber D, et al. Real-time sonoelastography of salivary glands for diagnosis and functional assessment of primary Sjögren's syndrome. Ultrasound in Med & Biol 2014; 40:2759–67. Disclosure of Interest: None declared